A Cross-Cultural Study of Organizational Work–Family Initiatives, Work Demands and Conflict, and Job-Related Outcomes among Working Parents across 24 Countries. (April 2022) - Hsiao, Hsinyi
To examine applicability of the work–family interface consisting of work–family initiatives, work demands, work–family conflict, and job-related outcomes developed in Western societies across countries with individualist and collectivist cultures, the present study used data collected by the International Social Survey Program (ISSP) in 2005 from 6878 parents in 24 countries through random sampling. Results from multigroup structural equation modeling analyses showed that parental work–family experiences are highly susceptible to cultural values and gender roles. These relationships among variables differed by gender across four groups ranging from high-individualism to high-collectivism. Fathers in highly individualist countries (e.g., Great Britain and the United States) were most affected by the work–family model, whereas mothers in highly collectivist countries (e.g., Mexico and the Philippines) were most influenced by the model. Findings of the present study highlight the importance of general and culture-specific practices for multinational organizations to help their employees address work–family issues.